IMPACT OF CLINICAL PHARMACIST DRIVEN COUNSELING TOWARDS POLY CYSTIC OVARIAN DISEASE AMONG COLLEGE STUDENTS (World Journal of Current Medical and Pharmaceutical Research, 2020)
Aim: A questionnaire based study to assess the knowledge of girls on PCOD and to create awareness in girls and to evaluate the effect of counseling program on the level of knowledge regarding PCOD among girls and to evaluate girls at risk. Subject&Methods: Observational prospective longitudinal survey carried out in 3 stages. Questionnaire consist of 30 questions in which 17 questions are used to evaluate knowledge & remaining 13 questions are used to evaluate the girls at risk by using Rotterdam criteria. Descriptive statistics were used.Results: The study was conducted in a population of 550 females of age group of 16- 24. The mean age of the students is 18.8 + 1.9.Only 9% of girls are having good knowledge regarding PCOD before the counseling, which was improved to 85.8% after counseling. This result shows the effectiveness of educational program which helps them to prevent infertility problems and helps in management of PCOD.Conclusion: It is important to create awareness about PCOD to the population, so that the future generation will be aware about PCOD and will be safe and stay healthy and educational program is effective in improving the knowledge of college girls. Furthermore efforts have to be developed to create the awareness.